Perbandingan Pemahaman Mahasiswa Akuntansi Dalam Pembelajaran Mengenai Perpajakan Secara Teori dan Praktik - Putri, Beryl Zya; Safira, Shella Rahma (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to analyze the comparison of accounting students' understanding in tax learning, both from theoretical and practical perspectives. Using a survey method, this research involved 31 accounting students from several universities in Indonesia who had taken tax courses. The results show that most students have a better understanding of tax theory than its practice. The main challenges faced include limited internship opportunities and insufficient use of real case studies in the learning process. Additionally, students struggle to comprehend the evolving tax regulations, especially due to the complex legal language used. To enhance students' understanding, integrating theory and practice needs to be strengthened by increasing practical opportunities through internships, simulations, and the use of technology in tax education. This study suggests that universities collaborate with industries to provide more practical experiences for students, preparing them better for the challenges of taxation in the professional world.